Understanding the experiences of relocatees during forced relocation in Chinese urban restructuring - Xin Li; Maarten van Ham; Reinout Kleinhans (A+BE: Architecture and the Built Environment)
Despite the massive forced relocation of residents during urban restructuring in China, there is no systematic overview regarding how residents experience the process and its outcomes. Most studies concerning urban restructuring in China directly equate forced relocation with displacement, which has a negative connotation. This exclusively negative view overlooks the multifaceted effects of forced relocation on relocatees. This paper aims to provide a better understanding of relocatees’ experienced during urban redevelopment in China by establishing a conceptual model in which the time sequence of events and their context are central, and by analysing the existing research on this topic about China. It conceptualises forced relocation as a process with various and changing socio-spatial implications over time, and as a specific type of residential mobility that occurs in the context of urban restructuring. As such, the paper presents a conceptual model that includes different stages and contexts to analyse the experiences of relocatees during and after forced relocation. It divides the process of forced relocation into a pre-demolition stage, a transitional stage and a post-relocation stage and investigates the social, economic, physical, psychological and behavioural dimensions of the experiences of relocatees as affected by the macro and micro context. As such, the conceptual model is used to structure the analysis of the existing literature about residents’ experiences and subsequently identify the gaps in the literature that should be addressed in future studies of forced relocation in the Chinese context.